2003
DOI: 10.1016/s0014-5793(03)01293-6
|View full text |Cite
|
Sign up to set email alerts
|

A left‐handed 31 helical conformation in the Alzheimer Aβ(12–28) peptide

Abstract: We show for the ¢rst time that the secondary structure of the Alzheimer L L-peptide is in a temperature-dependent equilibrium between an extended left-handed 3 1 helix and a £exible random coil conformation. Circular dichroism spectra, recorded at 0.03 mM peptide concentration, show that the equilibrium is shifted towards increasing left-handed 3 1 helix structure towards lower temperatures. High resolution nuclear magnetic resonance (NMR) spectroscopy has been used to study the Alzheimer peptide fragment AL L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 23 publications
8
69
0
Order By: Relevance
“…Jarvet et al (43) investigated A␤ [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] by CD and NMR and identified a substantial PPII population. We have recently arrived at a similar conclusion for the longer and more representative fragment A␤ by comparing the experimentally obtained amide IЈ band profile of the anisotropic Raman spectrum with simulation for various conformations assignable to the left-handed quadrant of the Ramachandran plot (44).…”
Section: Discussionmentioning
confidence: 99%
“…Jarvet et al (43) investigated A␤ [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] by CD and NMR and identified a substantial PPII population. We have recently arrived at a similar conclusion for the longer and more representative fragment A␤ by comparing the experimentally obtained amide IЈ band profile of the anisotropic Raman spectrum with simulation for various conformations assignable to the left-handed quadrant of the Ramachandran plot (44).…”
Section: Discussionmentioning
confidence: 99%
“…In order to stabilize the monomeric form of the peptide and reduce aggregation, SDS-d 25 micelles (SDS ¼ sodium dodecyl sulfate) were employed (39)(40)(41)(42). At this condition, the Aβ monomer adopts an α-helical conformation, which has been observed in solution and in contact with other biological molecules and may contribute to initial aggregation pathways leading to the formation of oligomers that have been proposed as the neurotoxic species in AD (5,(43)(44)(45)(46)(47). Therefore, the investigation of the possible interactions with the Aβ monomer using this model is valuable in evaluating the efficiency of our compounds to target and interact with Aβ species.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] This suggests that many IDPs undergo a structural change with increasing temperature. Different models have been put forward to explain this observation; however, the data do not decisively determine which explanation is correct, mainly because of the lack of atomic resolution information.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have identified structural changes upon heating that were interpreted mostly as formation of a-helices and to a minor extent to a loss of PPII structure. [20][21][22][23][24][25][26] The interpretation of the changes observed by CD spectroscopy is ambiguous. This is caused by the low resolution of this technique and the fact that structural changes in different segments may have spectroscopic contributions that cancel each other's signal.…”
Section: Introductionmentioning
confidence: 99%